WPŁYW ROZUMIENIA OSOBY NA KONCEPCJĘ KULTURY - Fotta, Peter (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Human capacity to knowledge and role within their culture depend primarily on whether culture itself contains so-called theory aspect that differentiates, or is potentialy being able to differentiate, between scientific, practical, artistic and religious knowledge. From a theoretical viewpoint we distinguish two neighbouring conceptions of human person. In the first instance, we focus on Cartezian-Kantian tradition within which awareness and intentional being obviates the border between the person and culture. Culture is seen as the urphenomenon of human life, as its vital necessity that allows for human life to be human. Culture is here seen as prafenomen human life and how vital necessity is a prerequisite for human life as a man Against this view, within the realistic philosophy we analyse the facticity of human existence and acts. Through actions the human being-as-person transcends nature, society and his own being. Human person as a subject is manifesting themselves in all spheres of culture. He exists autonomously, as a concrete individual being – the substance “in itself”. Culture does not exist autonomously. As an intentional being is a relational entity, whose primary mode of existence generates our intellectual act of knowledge.